A study on the green library practices of selected science high school libraries in Metro Manila - Azul, Michael M. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
Today, taking care of the environment is one of the most pressed agenda in the world and everyone's contribution towards a more environment friendly society isessential. Libraries are an integral part of society, thus, they are also called for to support this goal.